ADVERTISING AS SOCIAL AND CULTURAL PHENOMENON OF POST-MODERNITY - Іщук, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
A theoretical analysis of advertising and promotion is made with the help of the philosophy of Post-modernism. Some tendencies of advertising influence on the modern culture have been revealed.